Regional aspects of the development of largest enterprises in the Czech Republic - Sucháček, Jan; Seďa, Petr; Friedrich, Václav; Koutský, Jaroslav (Technological and Economic Development of Economy, 2017)
Location processes are constitutive for the formation of economic landscape. Largest enterprises represent one of the most important units of territorial economies. Their role is palpable mainly in the sphere of employment, technological level, value chains, competition as well as overall economic power. It is far from surprising that the weight of enterprise headquarters is higher than that of their affiliates. Therefore, the main objective of our article is to analyze and assess the development of spatial organization of one hundred largest enterprise head offices in the Czech Republic from both quantitative and qualitative perspectives. Due to data limitations, size of the enterprise is measured by its turnover. Spatial distribution of one hundred largest Czech enterprises and its development over time represent the focal point of our evaluation from quantitative point of view. The analysis was based upon annually published top 100 databases. Qualitative assessment is underpinned by the results of the questionnaire, which was focused on particular location factors accentuated by largest enterprises. Consistency analysis and exploratory factor analysis provide us with useful instrument for the evaluation of qualitative dimension of the issue and help us to conceptualize location preferences of largest enterprises in the country.